Effects of Antihypertensive Drugs and Gene Variants in the Renin-Angiotensin System - OGIHARA, Toshio; MOTONE, Motoharu; FUKUDA, Masayuki; KATSUYA, Tomohiro; ASAI, Takashi; RAKUGI, Hiromi; FU, Yuxiao; OHISHI, Mitsuru; IWASHIMA, Yoshio; SUGIMOTO, Ken; HATANAKA, Yasuko; HIGAKI, Jitsuo (Hypertension Research, 2001)
Many genes and environmental factors are involved in the pathogenesis of hypertension, but the exact cause of essential hypertension has not yet been clarified. Gene polymorphism of the renin-angiotensin system (RAS) is one of the candidates. In the current study, we examined whether there was a correlation between the gene polymorphisms in RAS and either the choice of antihypertensive drugs or their efficacy. Subjects with essential hypertension (n=299) were recruited from among the outpatients of Osaka University Hospital and provided their informed consent for genetic analysis. Physicians freely chose the antihypertensive drugs and adjusted its dose until the patient’s blood pressure was well controlled. The efficacy of each antihypertensive drug was estimated using the following formula: ΔBP=BP 1 (before treatment) - BP 2 (after treatment)/BP 1×100(%). Gene variants in RAS were determined using PCR or PCR-RFLP (restriction fragment of polymorphism). The gene polymorphism of RAS were not associated with ΔSBP or ΔDBP. However, the mean ΔSBP in subjects with a deletion homozygote of the angiotensin converting enzyme gene (ACE/DD) was significantly lower (p<0.05) than that in patients with an insertion/allele of the ACE gene. The gene polymorphisms of RAS did not significantly affect the choice of antihypertensive drugs. Even though gene polymorphism in the renin angiotensin system was not a major factor in the anti-hypertensive therapy, the determination of genotype might be of help in the management of essential hypertension. (Hypertens Res 2001; 24: 463-467)